Entrepreneurs’ Opinion Toward Tax Filing Service via the TaxRIS System in Xayabuli District, Xayabuli Province - Phounnaly, phayvanh; THAMMACHALER, Somphone; CHANTHAVONE, Thongphanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purposes of this study were: 1) to examine the knowledge and understanding of entrepreneurs in Xayabuli District regarding the tax filing service via the TaxRIS system; 2) to assess the level of entrepreneurs’ opinions on the tax filing service via the TaxRIS system in Xayabuli District; and 3) to compare the levels of entrepreneurs’ opinions on the TaxRIS tax filing service based on personal factors. The target group consisted of 78 entrepreneurs in Xayabuli District. Data were collected using questionnaires, and statistical methods including frequency, percentage, mean, standard deviation, t-test, and F-test were used for analysis. The research findings were as Entrepreneurs in Xayabuli District demonstrated a moderate level of understanding of the TaxRIS tax filing system. Entrepreneurs expressed a high level of agreement regarding the effectiveness of the TaxRIS system. Their opinions were ranked from highest to lowest in the following order: net benefit, service quality, intention to use, information quality, system quality, and user satisfaction. The comparison of opinions based on personal factors revealed significant differences: Entrepreneurs with different ages, marital statuses, education levels, and business incomes had differing opinions regarding the perceived net benefit. Differences in age and marital status were associated with varying opinions on intention to use. Business size, income, and duration influenced opinions on information quality. Business size and income affected opinions on service quality. Marital status was associated with differences in user satisfaction.